Activities and practices supported by the central library of the Federal University of Pará (Research, Society and Development, 2023)
The objective of this work is to analyze the environmental sustainability conditions of the central library of the university city Prof. José da Silveira Netto of the headquarters campus of the Federal University of Pará, based on the thermal, acoustic, accessibility, security, internal space, furniture, and comfort conditions. environmental, lighting, layout, emergency signaling and location of fire extinguishers. The research is characterized as applied and exploratory, qualitative, choosing the methods of documentary, bibliographic and case study research, as a methodological procedure for using data collected by means of questionnaires applied to users (librarians, technical administrative servers in education, stockholders and students) and bibliographic survey related to the topic. The results show that the central library needs to better adapt to sustainability conditions, therefore we conclude with some conclusions that the central library of UFPA needs to go through better times in its structure not related to environmental comfort. The authors of this research suggest merits considering the importance of users in the context of the university and that the analyzed environment is an example of a sustainable library to address the basic principles of environmental sustainability.